2019
DOI: 10.21037/tgh.2019.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for locally advanced hepatocellular carcinoma

Abstract: Liver cancer ranks fifth in incidence and fourth in overall cancer-related mortality, with approximately 854,000 new cases and 810,000 deaths per year worldwide. Hepatocellular carcinoma (HCC) accounts for 90% of these cases, and, over time, both the incidence and mortality of this cancer have been rising in many regions. Several staging systems are used to assess the extent of primary tumor, presence of metastasis, and underlying liver disease, and thereby aid in the definition of treatment strategies and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 146 publications
(231 reference statements)
0
14
0
Order By: Relevance
“…In the case of series 14a-d, the introduction of a phenyl or 2-methylphenyl group in 14a and 14b resulted in a more promising activity than the 4-bromophenyl derivatives 14c and 14d (IC50 = 25.88 and 26.16 μM, respectively vs. 112. 35 and 62.00 μM, respectively).…”
Section: In Vitro Anti-proliferative Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…In the case of series 14a-d, the introduction of a phenyl or 2-methylphenyl group in 14a and 14b resulted in a more promising activity than the 4-bromophenyl derivatives 14c and 14d (IC50 = 25.88 and 26.16 μM, respectively vs. 112. 35 and 62.00 μM, respectively).…”
Section: In Vitro Anti-proliferative Activitymentioning
confidence: 91%
“…Recently, it was reported that overexpression of VEGFR-2 in HCC promotes pathological angiogenesis [32,33]. Hence, the application of VEGFR-2 inhibitors in HCC is considered one of the most successful approaches to hinder the growth and spread of hepatic cancer cells [33][34][35].…”
mentioning
confidence: 99%
“…Stages in the development of HCC from initiation to metastasis to other regions of the liver and eventually to other tissues are summarized schematically in Figure 4 [ 3 , 10 , 59 ]. The development of HCC tumors is usually preceded by liver fibrosis and cirrhosis, although some HCCs develop without cirrhosis [ 1 , 3 , 10 , 60 ].…”
Section: The Pathology Of Hepatocellular Carcinomamentioning
confidence: 99%
“…2,3 Meanwhile, diverse treatment approaches involving a combination of various local therapies and systemic treatments have been administered in a sequential or concurrent manner. [4][5][6] We would like to report an extraordinary case of a patient who presented with a large HCC with main portal vein tumor thrombosis (PVTT) and showed long-term survival in spite of continuous recurrence. Moreover, the tumor was already ruptured at the time of presentation and the patient was hemodynamically unstable due to intraperitoneal massive bleeding.…”
Section: Introductionmentioning
confidence: 99%